Tattoos in the Wake of Trauma: Transforming Personal Stories of Suffering into Public Stories of Coping. Issue 10 (3rd October 2021) - Crompton, Laura; Plotkin Amrami, Galia; Tsur, Noga; Solomon, Zahava
ABSTRACT: Growing numbers of trauma survivors have chosen to cope with their ongoing invisible wounds through tattooing their bodies. This phenomenon includes individuals as well as organized and documented projects held in public spaces. The topic of body modification through tattoos has benefited from an explosion in academic interest; however, there has been little scholarly attention directed at examining how tattoo practices may be understood as a means of coping with trauma within a contemporary cultural context. While drawing on psychological and cultural studies' perspectives we explored the meanings attributed to tattoos by trauma survivors. Analyzing documented personal accounts of tattooed survivors in different countries, we illustrated how being tattooed appears to be a personal way of coping with trauma as well as a cultural practice of meaning making. The meanings attributed by trauma survivors' included: exposing their trauma for recognition, witnessing, meaningfulness of the tattoo, connection, control, and transformation. The meaning-making process appears to be continuous and dynamic, shaped by psychological responses, social interactions, and cultural narratives.